FAMILY PSYCHOLOGY IN FORMING MORAL AND MORAL IMMUNITY AGAINST INFORMATION ATTACK. GENDER STEREOTYPES: THE INFLUENCE OF CHILDREN'S UPbringing AND SOCIAL CONSCIOUSNESS (Universal International Scientific Journal, 2026)
This article analyzes the importance of family psychology in the formation of spiritual and moral immunity in the conditions of various information attacks affecting the consciousness of the younger generation in the modern information space. The spiritual values ​​formed in the family environment, methods of upbringing based on the example of parents, and psychological factors in the process of socialization of the child are highlighted. The article also examines the impact of gender stereotypes on child upbringing and social consciousness formed in society from a scientific point of view. It is argued that ensuring a healthy psychological climate in the family environment is an important factor in protecting young people from various negative information influences.
Keywords: information attack; spiritual immunity; family psychology